Truncated variant rs373056577 confers increased risk of type 2 diabetes and missense variant rs121912717 is associated with hypertriglyceridemia in Bangladeshi population - Shomoita Sayed; Abdullah Al Saba; Imrul Hasan; Rafia Rahat; Mohammad Sayem; Akio Ebihara; A.H.M. Nurun Nabi (Metabolism Open)
This study investigates the association of allelic and genotypic variations of rs121912717 and rs373056577 within APOA1 and APOA2 genes, respectively with the risk of type 2 diabetes (T2D). In this cross-sectional study, real-time quantitative PCR with specific Taqman probes was used to determine the genotypic and allelic frequencies of rs121912717 and rs373056577 in 300 unrelated Bangladeshi individuals (Healthy = 144, T2D patients = 156). Logistic regression analysis was performed to investigate the association of genotypic and allelic frequencies of these SNPs with respect to T2D under different inheritance models. Neither allelic nor genotypic frequencies of rs121912717 within APOA1 showed any significant association with T2D. Genotypes with respect to rs373056577 within APOA2 showed significant association with the risk of T2D under co-dominant heterozygous model (GG vs GA) [OR (95 %CI): 2.64 (1.32–5.59), p = 0.008], dominant [OR (95 %CI): 2.31 (1.24–4.49), p = 0.01] and over-dominant [OR (95 %CI): 2.62 (1.31–5.53), p = 0.008] models without adjusting for age, gender and BMI. After adjusting for age, gender and BMI, the A allele of rs373056577 showed significant association with T2D only in the dominant model [OR (95 %CI): 3.20 (1.12–10.51), p = 0.04]. Also, A allele of rs373056577 demonstrated significant association with the risk of T2D compared to allele G with [OR (95 %CI): 2.90 (1.15–8.14), p = 0.03] and without adjusting for confounders [OR (95 %CI): 1.97 (1.14–3.52), p = 0.02]. The genotypic frequency was significantly associated with T2D in codominant, dominant, and overdominant models in male participants when a gender-stratified analysis was conducted for rs373056577. However, when the logistic regression analysis was adjusted for age and BMI, the association was not significant in any of the models with respect to rs373056577 for male participants. On the other hand, gender-stratified regression analyses revealed no significant association with T2D before and after adjusting for age and BMI with respect to both allelic and genotypic frequencies of rs121912717. Individuals with CT genotype of rs121912717 had significantly higher triglyceride levels (322.2 mg/dL) compared to those harboring CC genotype (202.8 mg/dL) with or without adjusting for age, gender, BMI and disease status of the study participants. In conclusion, this study revealed that individuals harboring the allele A of rs373056577 possessed an increased risk of developing T2D and individuals having CT genotype of rs121912717 had increased triglyceride levels. The result of this study needs to be validated in a larger cohort for a more robust assessment.